Recycling of landfill wastes (tyres, plastics and glass) in construction – A review on global waste generation, performance, application and future opportunities - Ferdous, Wahid; Manalo, Allan; Siddique, Rafat; Mendis, Priyan; Zhuge, Yan; Wong, Hong S.; Lokuge, Weena; Aravinthan, Thiru; Schubel, Peter (Resources, conservation and recycling, 2021)
•Currently 75% of tyres, 55% of plastics, 75% of glass, 47% of fly ash and 60% of C&D wastes are disposed in landfills.•Crumb rubber in concrete can degrade physical and mechanical properties but improve thermal and dynamic properties.•Recycling is the best practice of managing waste plastics followed by landfill and incineration.•Waste glass could be a good alternative to replace natural sands in concrete.•Recycling 10,000 tons of waste can create 9.2 jobs while this number is only 2.8 if disposed in landfill. The world is moving towards a circular economy that focuses on reducing wastes and keeping materials in use for the longest time possible. This paper critically reviewed three of the largest volume of landfill waste materials (tyres, plastics and glass) that are becoming a major concern for many countries. At present, crumb rubbers (from tyres) and glass sands (from crushed waste glass) are being used in concrete and road constructions while plastics are often used in manufacturing civil structures. However, only 10% tyres, 19.5% plastics and 21% glass are currently recycled globally. The massive volume of remaining unused wastes goes to landfill creating environmental problems. Therefore, finding new strategies of utilising these landfill wastes is vital. The global and country specific production, recycling and landfilling rates of these waste are summarised to understand the present situation of global waste crisis. Future strategies for improved waste management, potential investment and research directions are highlighted. New options for recycling wastes tyres, plastics and glass in construction are also presented to provide practical and economical solutions to extract maximum value and ensure their continued use in a closed loop system.